2006
DOI: 10.1136/ijgc-00009577-200605000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Prime-boost vaccination strategy in women with high-grade, noncervical anogenital intraepithelial neoplasia: clinical results from a multicenter phase II trial

Abstract: The objective of this study was to determine the clinical effectiveness of a prime-boost human papillomavirus (HPV) vaccine regimen. A nonrandomized phase II prime-boost vaccine trial was conducted. Women with biopsy-proven anogenital intraepithelial neoplasia (AGIN) 3 were vaccinated with three doses of a recombinant fusion protein comprising HPV 16, E6/E7/L2 (TA-CIN) followed by one dose of a recombinant vaccinia virus encoding HPV 16 and 18 E6/E7 (TA-HPV). Clinical responses were evaluated by serial photogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…No serious adverse effects were observed in all patients; in addition, 5 out of 29 patients showed increased HPV-16-specific T cell mediated immune responses. However, the result does not show significant advantage over single TA-HPV vaccination [78]. In another prime-boost regimen, ten patients with HPV-16+ high-grade vulvar intraepithelial neoplasia were primed with TA-HPV and boosted with TA-CIN.…”
Section: Protein-based Vaccinesmentioning
confidence: 89%
See 2 more Smart Citations
“…No serious adverse effects were observed in all patients; in addition, 5 out of 29 patients showed increased HPV-16-specific T cell mediated immune responses. However, the result does not show significant advantage over single TA-HPV vaccination [78]. In another prime-boost regimen, ten patients with HPV-16+ high-grade vulvar intraepithelial neoplasia were primed with TA-HPV and boosted with TA-CIN.…”
Section: Protein-based Vaccinesmentioning
confidence: 89%
“…In a Phase I trial, vaccination with TA-CIN was shown to induce antibody responses against L2 in all patients and T cell immunity against HPV-16 E6 and E7 oncoproteins in 8 out of 11 healthy patients receiving the highest dose, proving to be safe and immunogenic [66]. Phase II trials have focused on using TA-CIN as part of a prime-boost regimen with TA-HPV [77][78][79] since preclinical studies suggested this was a more effective regimen [80]. For example, in a Phase II clinical trial, HPV protein-based vaccine, TA-CIN, was used for priming and a recombinant vaccinia virus encoding HPV-16/18, E6/E7 fusion protein (TA-HPV) was used for boosting in 29 patients with anogenital intraepithelial neoplasia.…”
Section: Protein-based Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the enhanced efficacy of the vaccines using a prime-boost regimen in preclinical models, these combinatorial HPV vaccines have entered clinical trials. A clinical trial in patients with anogenital intraepithelial neoplasia demonstrated that a prime-boost regimen consisting of HPV-16 L2/E6/E7 fusion protein (TA-CIN) followed by a recombinant vaccinia virus encoding the E6/ E7 fusion proteins of HPV types-16 and -18 (TA-HPV) could enhance HPV-16 antigen-specific T cell responses which correlated with clinical regression [116,117].…”
Section: Future Directionsmentioning
confidence: 99%
“…While this primeboost regimen induced cellular immunity in VIN patients, no direct correlation between clinical and immunological responses was seen. Moreover, one of the first randomized Phase II clinical trials of a prime-boost vaccination regimen using heterologous HPV vaccines (TA-CIN followed by TA-HPV) in the management of anogenital lesions failed to demonstrate any significant advantages of the prime-boost approach over single TA-HPV vaccination [131].…”
Section: Prime-boost Strategymentioning
confidence: 99%